Air-Entraining Effect on Rheological Properties of Cement-Based Mixtures - Aigerim Tolegenova; Gintautas Skripkiunas; Lyudmyla Rishko; Kenzhebek Akmalaiuly (Advances in Materials Science and Engineering)
The rheological properties and stability of cement-based materials determine the technological properties of concrete mixtures and significantly influence concrete properties. Polycarboxylate ether (PCE) and other plasticizing admixtures are widely used in construction practice to plasticize concrete mixtures. Experimental research on the rheological characteristics of cement mortar modified with PCE and air-entraining admixtures (AIRs) was carried out with a rotation rheometer with coaxial cylinders and water bleeding tests. Herschel–Buckley or modified Bingham models were used to approximate experimental flow curves and assess rheological parameters such as yield stress, plastic viscosity, and shear thinning/thickening index. The rheological test was carried out at 5 and 90 min after mixing the cement mortar. The rheological test established that the modification of cement mortar by PCE in a dosage of 0.2% (in dry material) leads to a decrease in plastic viscosity of 25.0% with a reduction in water demand of 18% for the same workability. Modification of cement mortar by AIR in 0.3% dosage leads to a decrease in yield stress by 37.7% and a decrease in plastic viscosity by 35.4% compared to the control specimen without PCE. The combined modification by PCE and AIR admixtures shows a synergistic effect. It leads to a significant decrease in yield stress of cement mortar by 92.2% and a decrease in plastic viscosity to about 0  Pa·s. In addition, there is a significant coefficient of water bleeding reduction up to 0%, when additional water reduction was carried out in the mixture while maintaining the same workability. The cement mortar, with or without PCE and AIR, exhibited shear-thinning characteristics for up to 90 min after mixing. The solid, liquid, and gas (air) phases’ influence yield stress and plastic viscosity in the analysis mixtures are presented in this paper. It has been established that a modified exponential Mooney dependency can be used to predict the yield stress and plastic viscosity of the modified cement mortar (both plasticized and air-entrained).